Hubungan antara Pendapatan Daerah, Belanja Daerah dan Produk Domestik Regional Bruto (PDRB) di Provinsi Kepulauan Bangka Belitung dengan Analisis Panel Vector Auto Regression (PVAR) - Husril Husril; Nizwan Zukhri; Devi Valeriani (Jurnal Ekonomi Pembangunan, 2021)
This study aims to analyze and determine the relationship between Regional Income, Regional Expenditures and Gross Regional Domestic Product (GRDP) in the Province of the Bangka Belitung Islands. The type of research used is quantitative. The data sources of this research are secondary data obtained from the Central Statistics Agency (BPS) and the Directorate General of Treasury (DJPB). The data used is on Regional Income, Regional Expenditure and GRDP in all districts/cities of the Bangka Belitung Islands Province in 2014-2019. The data analysis performed was analysis Panel Vector Auto Regression (PVAR). The results showed no causal relationship between regional income and GRDP in the Province of the Bangka Belitung Islands, with probability values of 0.94 and 0.87. Meanwhile, there is a one-way relationship between regional income and regional expenditure in the Province of the Bangka Belitung Islands with a probability value of 0.005 and 0.16, and there is no causal relationship between regional expenditure and GRDP in the Province of the Bangka Belitung Islands with a probability value of 0.98 and 0.96.